The Influence of The Cellphone Confiscation Policy During KBM on The Orderly KBM Process at Madrasah Aliyah Negeri 1 Jember - Alifana, Fairus Tahta; Maziyya Naila Rif'ah; Amalia Wanda Mega R.; Imam Hefni Mubarok; Firman Hakiki; Rofiq Hidayat (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2024)
The aim of this research is to measure the extent to which confiscation of cellphones during teaching and learning (KBM) affects the teaching and learning process at MAN 1 Jember. This research uses a quantitative approach with a comparative causal research type and collects data through questionnaires designed for subject teachers and homeroom teachers. The results of this correlation analysis show that there is a strong and significant relationship between the cellphone confiscation policy variable and the KBM orderly variable. These findings provide empirical evidence that the instruments used are valid and reliable in measuring the constructs studied. Based on the results of the t test, the calculated t value for the Orderly Learning Process variable is 7.714, with a significance value (Sig.) of less than 0.05, it can be concluded that the cellphone confiscation policy variable has a positive and significant influence on the creation of the teaching and learning process. This means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Therefore, it can be stated that the cellphone confiscation policy has an influence in creating an orderly KBM process.